Dynamic interaction of a prestressed nonlinear elastic layer and a half-plane - Akbarov, SD; Ozisik, M (SPRINGER, 2004)
Generalized Rayleigh waves propagating in a prestressed layer on a prestressed half-plane under plane-strain conditions are studied using the piecewise-homogeneous model and the three-dimensional linearized theory of elasticity. The constitutive relations of the layer and half-plane include the Murnaghan potential. Numerical results have been obtained for two materials: bronze for the layer and steel for the half-plane.
Keywords: piecewise-homogeneous body; three-dimensional linearized theory of elasticity; prestressed layer; Rayleigh wave; Murnaghan potential; WAVES; STRESSES; SOLIDS; Mechanics